Kinetics on Anaerobic Digestion and Wastewater Treatment of Chicken Slaughterhouse - Laowansiri, Sunantha; Tharasena, Busaba; Khamhok, Sukanya (Journal of Food Health and Bioenvironmental Science, 2018)
The kinetics of anaerobic mixed culture treatment of chicken slaughterhouse wastewater was investigated in this research. Experiments were conducted in the serum bottle containing 90 ml of chicken slaughterhouse wastewater including 10 ml sludge (2,000 mg/l mixed liquor volatile suspended solids, MLVSS) from upflow anaerobic sludge blanket (UASB) system. The bottles were operated in anaerobic condition with the chicken slaughterhouse wastewater at various chemical oxygen demand (COD) concentrations of 400, 800, 1200 and 1600 mg/l at pH 7.00±0.02. The serum bottles were incubated for 30 days at 37±1 °C without shaking. Based on the data, the order kinetics of the reaction were found in different COD concentrations of organic matter in chicken slaughterhouse wastewater treatment. The reaction order in the degradation of higher COD concentrations (800, 1200 and 1600 mg/l) of chicken slaughterhouse wastewater treatment is a fit for first order kinetic model. On the other hand, the COD degradation of the anaerobic treatment of chicken slaughterhouse wastewater at low COD concentration (400 mg/l) appeared to be close to the second order. The increasing of COD and color removal efficiencies of the slaughterhouse wastewater treatment was observed with a greater concentration of COD. The maximum COD and color removal efficiencies (90.40 and 48.96%, respectively) were found at the 1600 mg COD/l. Moreover, the biogas production increased with an increase in COD concentration of the wastewater and incubation time. The highest biogas production reached was 267.0 ml biogas volume (64.03% CH4) with wastewater treatment of COD concentration at 1600 mg/l for 30 days.